Outcome of Surgical Management in Spontaneous Supratentorial Intracerebral Hemorrhage Patients: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Management of spontaneous supratentorial intracerebral hemorrhage is crucial.Objective: The purpose of the present study was to compare the outcome of surgery in relation to conservative management of spontaneous supratentorial intracerebral hemorrhage.Methodology: This was a single centred, parallel randomized control trial which was conducted in the Department of Neurosurgery at Dhaka Medical College and Hospital from January 2010 to October 2011 for a period of one year and ten months. All hypertensive patients with spontaneous supratentorial intracerebral hemorrhage who were admitted within 48 hours of stroke in Neurosurgery Department during the study period were considered as a study population. Patients underwent surgery was considered as group I and patients those who did not give the consent for operation were treated conservatively was considered as group II. Surgery and conservative groups were matched in age.Result: A total of 31 patients were enrolled in this study. Fourteen (14) patients underwent surgical evacuation while seventeen (17) patients those who didn’t give consent for operation were selected for conservative therapy. The distribution of the study patients according to GOS (30 days) that 6(42.9%) and 10 (58.8%) patients in surgery and conservatively managed patients were dead respectively; however, 4(28.6%) patients in surgery and 3(17.6%) patient in conservative group had good recovery. Besides, 2(14.3%) surgery patients and 3(17.6%) conservative patients were severe disabled. Moreover, 2(14.3%) surgery patients and 1(5.9%) conservative patients were moderately disabled.Conclusion: In conclusion surgical evacuation of spontaneous supratentorial intracerebral hemorrhage has a benefit on outcome compared to conservative medical treatment.Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 37-41